Acknowledging Landscape Connection: Using Sense of Place and Cultural and Customary Landscape Management to Enhance Landscape Ecological Theoretical Frameworks - Diane Pearson; Julian Gorman (Land, 2023)
Landscapes are important socio-ecological systems. They are widely researched through landscape ecology to aid conservation and environmental management efforts, yet these efforts are not always as successful as they could be in terms of on-the-ground impact. Increasingly when considering conservation, it is being recognized that indigenously managed landscapes have slower rates of biodiversity loss and better environmental outcomes. Local knowledge and connection to the landscape can play a significant part in successfully managing these landscapes. Acknowledging that stewardship of the landscape is more effective when people are a part of the landscape with deep-rooted connection to place is important for understanding the significance of traditional ecological knowledge and the implementation of indigenous-led action. It has also been shown that researchers who have a stronger sense of place and connection to landscapes can also drive initiatives that have better environmental outcomes. This means that human connections to landscapes are important for management strategies, and a better understanding of the human cognition of landscapes is necessary in landscape ecological theoretical frameworks. This review paper explores literature that acknowledges cultural perspectives and cognition of landscapes and how this relates to landscape ecology. It makes recommendations about how landscape ecology can contribute towards better on-the-ground outcomes by embracing more effective mechanisms of collaboration and participation to incorporate local and indigenous knowledge.